The effect of CYP7B1 polymorphisms on the risk of coronary heart disease in Hainan Han population - Tiebiao Liang; Xianbo Zhang; Anshan Liang; Haiqing Wu; Qi Wang; Jun He; Ming Long; Tianbo Jin (BMC, 2021)
Abstract Background Coronary heart disease (CHD) is the leading cause of human death worldwide. Genetic factors play an important role in the occurrence of CHD. Our study is designed to investigate the influence of CYP7B1 polymorphisms on CHD risk. Methods In this case-control study, 508 CHD patients and 510 healthy individuals were recruited to determine the correlation between CYP7B1 polymorphisms (rs7836768, rs6472155, and rs2980003) and CHD risk. The associations were evaluated by computing odds ratios (OR) and 95% confidence intervals (CI) with logistic regression analysis. The association between SNP-SNP interaction and CHD susceptibility was carried out by multifactor dimensionality reduction analyses. Results Our study found that rs6472155 is significantly associated with an increased risk of CHD in age > 60 years (OR 2.20, 95% CI = 1.07-4.49, p = 0.031), women (OR 3.17, 95% CI = 1.19-8.44, p = 0.021), and non-smokers (3.43, 95% CI = 1.16-10.09, p = 0.025). Rs2980003 polymorphism has a lower risk of CHD in drinkers (OR 0.47, 95% CI = 0.24-0.91, p = 0.025). Further analyses based on false-positive report probability validated these significant results. Besides, it was found that rs6472155 polymorphism was associated with uric acid level (p = 0.034). Conclusion Our study indicated that CYP7B1 polymorphisms are related to the risk of CHD, which provides a new perspective for prevent of CHD.